Pengaruh Literasi Keuangan, Fintech Payment, dan Gaya Hidup terhadap Perilaku Konsumtif Generasi Z - Kristianing, Endang; Purnamasar, Endah Dewi; Setiawan, Budi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
The rapid development of financial technology and lifestyle changes in the digital era have increased consumptive behavior among Generation Z, potentially leading to long-term financial problems if not supported by adequate financial literacy. This study aims to analyze the effect of financial literacy, fintech payment, and lifestyle on the consumptive behavior of Generation Z in Palembang City. This research employs a quantitative method with a survey approach involving 145 respondents selected using purposive sampling techniques. Data were analyzed using multiple linear regression with the assistance of SPSS, including descriptive statistical analysis, classical assumption tests, and hypothesis testing (t-test and F-test). The results indicate that financial literacy has a negative and significant effect on consumptive behavior (p < 0.05), fintech payment has a positive and significant effect (p < 0.05), and lifestyle also has a positive and significant effect (p < 0.05). Simultaneously, all variables have a significant effect on consumptive behavior (F-test, p < 0.05). These findings highlight the importance of improving financial literacy and controlling fintech usage and lifestyle to reduce consumptive behavior among Generation Z.